Faktor Rendahnya Sengketa Ekonomi Syariah Di Pengadilan Agama Padang - Hafizh Adz Dzikri; Bintang Mandala Karyudi; Pradana Budi Setiawan; Melia Rosa; Mhd Ikbal (Lex Et Lustitia, 2026)
The development of the sharia economy in Indonesia has grown rapidly, as shown by the increasing number of Islamic banks, Islamic insurance companies, and businesses based on sharia contracts. According to data from Otoritas Jasa Keuangan, public interest in the sharia economic system continues to increase, which also raises the potential for sharia economic disputes. However, the number of sharia economic cases submitted to Pengadilan Agama Padang remains very low. This condition needs further study to identify its causes. This research aims to analyze the factors causing the low number of sharia economic disputes submitted to the Religious Court of Padang. The study uses an empirical juridical method with a descriptive analytical approach. Data were collected through observation and literature study. The research examines legal regulations concerning the authority of Religious Courts in resolving sharia economic disputes and compares them with conditions found in practice. The results show that the low number of cases is influenced by limited public understanding of the Religious Court’s authority, preference for non-litigation dispute resolution, limited sharia-based business practices, and public trust in judicial institutions.